Mini Fluid Challenge dan Pendekatan Focus sebagai Panduan Resusitasi - Riyanti Kasim; Syafri Kamsul Arief (Syntax Corporation Indonesia, 2021)
Fluid resuscitation plays a crucial role in the management of patients who experience acute circulatory failure in the intensive care unit. Adequate fluid resuscitation is an important issue because excessive fluid resuscitation can cause electrolyte disturbances and coagulation disorders, but improper volume restrictions can lead to low cardiac output or improper use of vasopressor or inotropic drugs. The purpose of focus examination is to provide timely and repeatable diagnostic information at the time a question arises. The methods carried out from this study are mini fluid challenge case study methods and focus approaches as a resuscitation guide. In an observational study conducted by Husain et al in 220 patients in intensive care units, use of FoCUS by handheld ultrasound devices was found to be associated with much lower fluid prescriptions (49 vs. 66 mL/kg, p = 0.01) and more use of dobuttamine (22 vs. 12%, p = 0.01) than the standardly managed historical control group. The correct Fluid Chalengee technique can maximize positive and negative predictive values by using two main components: the amount of fluid given and the duration of administration where the recommended optimal volume is 4ml/KgBB.